2011
DOI: 10.1007/s00595-010-4459-x
|View full text |Cite
|
Sign up to set email alerts
|

Mid- to long-term outcomes of cardiovascular tissue replacements utilizing homografts harvested and stored at Japanese institutional tissue banks

Abstract: Subcoronary implantation should probably be abandoned for routine aortic valve replacement, but the continued use of homografts will provide valuable alternatives for patients with active infectious cardiovascular diseases. For the Ross operation, pulmonary valve homografts showed good durability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…In contrast, previous reports, including one from our institution, showed that full-root implantation demonstrated durability similar to or greater than that observed for subcoronary implantation. 5,22,23 One should consider several reasons for such a contrary finding. First, previous reports analyzed risk factors for reintervention, whereas this study analyzed each pathology to clarify risk factors.…”
Section: Discussionmentioning
confidence: 93%
“…In contrast, previous reports, including one from our institution, showed that full-root implantation demonstrated durability similar to or greater than that observed for subcoronary implantation. 5,22,23 One should consider several reasons for such a contrary finding. First, previous reports analyzed risk factors for reintervention, whereas this study analyzed each pathology to clarify risk factors.…”
Section: Discussionmentioning
confidence: 93%
“…For patients requiring revascularization surgery, unavailability of autologous bypass grafts may lead to loss of an opportunity for appropriate therapy and consequent poor prognosis. Although cryopreserved arterial allografts can be a surrogate for autologous small-caliber grafts with acceptable long-term patency, the availability is rather limited because of the shortage of donors and insufficient operation of organ / tissue banks to preserve and provide allografts [15][16][17]. The present study was designed to address this healthcare problem through validating the feasibility of xenogeneic implantation of HHP-decellularized vascular grafts using bovine arterial grafts and a porcine carotid arterial interpose model.…”
Section: Semmentioning
confidence: 99%
“…Good long-term outcomes of aortic replacement with homograft for infectious aortic disease have been demonstrated. 5) However, in this particular reported case, we applied aortic replacement using a standard prosthetic graft due to the emergent situation under the limited availability of a homograft.…”
Section: Discussionmentioning
confidence: 99%